Avaliação citopatológica, imunocitoquímica e teste do cometa do lavado vesical de bovinos com hematúria enzoótica - Azevedo, Marcel Arcanjo Silva (2013)
The bovine enzootic haematuria (BEH) is a chronic disease caused by Pteridium aquilinum and is characterized by the formation of non-neoplastic and neoplastic lesions in the bladder of the affected animals and has no specific treatment. In the southern region of the Espírito Santo, Brazil, this disease has a high prevalence and is responsible for major economic losses in dairy cattle, resulting from late diagnosis of the disease. Cytology associated with the use of biomarkers could aid in the early diagnosis of this disease. The aim of the study was to evaluate lesions bladders of cattle associated with enzootic hematuria through cytological techniques, immunocytochemistry and comet assay, for the diagnosis of early cellular damage caused by the disease. The study was divided into two experiments. In experiment 1, to standardize the harvesting technique, obtain samples and perform cytology of the bovine washing urinary bladder with BEH, were used 10 cattle, adult females divided into two groups. In group A was recovered all the liquid infused in the bladder, in group B, only the last liquid was recovered. In experiment 2, the cells obtained by bovine washing urinary bladder and were evaluated by immunocytochemistry using anti-p53 and comet assay and were used 10 cattle, adult females, divided in two groups of five animals, five healthy and five with BEH. The material was fixed and subjected to tests cytological, immunocytochemical and comet assay and evaluated microscopically. Data were analyzed using descriptive statistics, analysis of variance and nonparametric Kolmogorov-Smirnov test. Regarding the number of inflammatory cells and epithelial cells obtained per sample revealed that the two groups of experiment 1, all animals had more inflammatory cells than epithelial cells, however, there was no difference between the type of washing taken. The epithelial cells were found in 60% of cases and the alterations observed were discretes and cannot classify any sample as hyperplastic or neoplastic. In experiment 2, we observed positive immunostaining of p53 in only 20% of the samples, one of healthy animal and another animal with BEH. The comet assay revealed that both the samples of healthy animals as well as in animals positive for BEH not observed migrating nuclear fragments. Data from this study showed that the cytological examination of bovine washing urinary bladder may aid in the diagnosis of BEH and the two harvesting methods employed were adequate for obtaining viable samples. Cytology allowed the identification of non-neoplastic lesions predominantly inflammatory and immunocytochemistry technique with the expression of p53 as well as comet assay revealed no important cell damage since the animals used in the experiment had no neoplastic lesions